Uma proposta de inclusão do xadrez como estratégia didática na formação de professores de matemática no ensino superior - Horta, Thiago dos Santos (2020)
Mathematical skills deficiency of Brazilian students was evident in the last diagnosis of Saeb and Pisa assessment programmes. This seems to be a reflection of the deficiency in teacher education in Mathematics, especially mainly regarding the use of diverse methodologies and pedagogical tools. Because chess is a game that develops mathematical thinking, it can be used as a pedagogical tool. A bibliographic research was conducted in CAPES databases to investigate academic production in Brazil on the use of chess as a pedagogical tool, especially in math classes, as well as a survey of the main sports regulatory entities in the country, events in the area and public school projects in which chess was used for educational purposes. It was observed that the current chess scenario in the country seems to lack national regulation, especially with regard to the training of chess teachers. Based on this scenario, a curricular change was proposed through the creation of a discipline in which chess is used as a didactic strategy in Mathematics Licentiate courses and, for this proposal, the theoretical basis was the Activity Theory. This way, it is intended to contribute to the improvement of the teacher education of graduates in Mathematics so that they can leave the undergraduate program better able to include chess as a pedagogical tool in the school context, which can lead to an improvement in the levels of learning in the discipline of mathematics as a whole in basic education.